Making Medicaid managed care research relevant. - Gold, M (1999)
OBJECTIVE: To help researchers better understand Medicaid managed care and the kinds of research studies that will be both feasible and of value to policymakers and program staff. The article builds on our experience researching Medicaid managed care to provide insight for researchers who want to be policy relevant. PRINCIPAL FINDINGS: We draw four lessons from our work on Medicaid managed care in seven states. First, these are complex programs that differ substantially across states. Second, each program faces common challenges and issues. The need to address common design elements involving program eligibility, managed care and provider contracting, beneficiary enrollment, education, marketing, and administration and oversight provides a vehicle that researchers can use to help understand states and to provide them with relevant insight. Third, well-designed case studies can provide invaluable descriptive insights. Such case studies suggest that providing effective descriptions of state programs and experience, monitoring information on program performance and tradeoffs, and insight on implementation and design are all valuable products of such studies that have considerable potential to be converted into policy-actionable advice. And fourth, some questions demand impact studies but the structure of Medicaid managed care poses major barriers to such studies. CONCLUSIONS: Many challenges confront researchers seeking to develop policy-relevant research on managed care. Researchers need to confront these challenges in turn by developing second-best approaches that will provide timely insight into important questions in a relatively defensible and rigorous way in the face of many constraints. If researchers do not, others will, and researchers may find their contributions limited in important areas for policy debate.